2023
DOI: 10.1101/2023.08.22.23294416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 shedding and evolution in immunocompromised hosts during the Omicron period: a multicenter prospective analysis

Zoe Raglow,
Diya Surie,
James D. Chappell
et al.

Abstract: Background: Prolonged SARS-CoV-2 infections in immunocompromised hosts may predict or source the emergence of highly mutated variants. The types of immunosuppression placing patients at highest risk for prolonged infection and associated intrahost viral evolution remain unclear. Methods: Adults aged >18 years were enrolled at 5 hospitals and followed from 4/11/2022-2/1/2023. Eligible patients were SARS-CoV-2 positive in the previous 14 days and had a moderate or severely immunocompromising condition or trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…7d , p-value = 0.043 Mann Whitney U), indicating that purifying selection is occurring in the CD4+/CD8+ tandem depleted mice. Further, the rates observed in our mouse isolates fall into similar ranges observed in immunocompromised individuals with prolonged infections (≥21 days) 46 . Over 76% of the iSNVs were C-to-T transitions ( Fig.…”
Section: Resultssupporting
confidence: 79%
“…7d , p-value = 0.043 Mann Whitney U), indicating that purifying selection is occurring in the CD4+/CD8+ tandem depleted mice. Further, the rates observed in our mouse isolates fall into similar ranges observed in immunocompromised individuals with prolonged infections (≥21 days) 46 . Over 76% of the iSNVs were C-to-T transitions ( Fig.…”
Section: Resultssupporting
confidence: 79%
“…A meta-analysis study of SARS-CoV-2 persistent infection individuals showed that SARS-CoV-2 evolution was significantly faster in these persistent infected immunocompromised patients than that in the general human population 26 . A recent cohort study also reported that although prolonged replication-competent Omicron SARS-CoV-2 infections were uncommon, the within-host evolution reported an increased nonsynonymous mutation rate in persistent patients compared to short infections, where the persistently infected individuals accumulated globally distinct Spike mutations 27 . Animal spillover and human-to-animal SARS-CoV-2 spillback have been frequently reported 28 .…”
Section: Discussion/conclusionmentioning
confidence: 98%
“…A number of these mutations (K356, V445, G446, N450, L452, and P621) were also observed in omicron sub-lineages within immunocompromised patients. This may indicate that reduced immune functions within some individuals may be a source of highly mutated SARS-CoV2 lineages (31, 32). BA.2.86 has also evolved several descendants including JN.1 which harbors three mutations in non S-proteins and a hallmark S455L mutation in the spike protein (2).…”
Section: Discussionmentioning
confidence: 99%